The Avholdsmann: The Life and Literature of Waldemar Ager, 1869-1941 - Hanson, Andrew (My University, 2015)
As a young man, Waldemar Ager was one of countless immigrants who saw opportunity in the logging community of Eau Claire, Wisconsin, during the latter half of the nineteenth century. While many immigrants believed that the lumber industry was their salvation, Ager found his calling by bringing his voice into the temperance movement. With stops in Chicago, Illinois, and Milwaukee, Wisconsin, Ager learned many of his temperance beliefs through life experiences both in Norway and the United States. During his time in Eau Claire, Ager played an important role in the city's temperance movement. By writing creative newspaper articles, short stories, and novels, Ager championed the use of literature in defending the importance of temperance. In addition to his pro-temperance penmanship, Ager also found success by establishing temperance organizations, giving anti-alcohol lectures, and by joining the Prohibition Party. Ager believed in, and fought for a society free from any burdens, including alcohol. While Ager's attempts to preserve Norwegian heritage have earned his works a great deal of respect, his beliefs on alcohol as seen through his literature, remain obscure. Despite receiving some coverage, the works that do mention his beliefs on alcohol are dated and brief. By studying a large number of Ager's writings, this study is charged with the task of shedding more light on Waldemar Ager, his life, and his anti-alcohol literature.
Keywords: Norwegians--United States; Prohibition--Wisconsin--History; Temperance--Wisconsin--History; Temperance in literature